HILITE – Ion Trap for Studies with Intense Laser Pulses. (August 2015) - Ringleb, S; Vogel, M; Kumar, S; Quint, W; Paulus, G G; Stöhlker, Th
Synopsis: We present our Penning Trap setup which is designed for capture, confinement and preparation of well-defined ion clouds for use in experiments with high-intensity lasers. We explain the experimental setup and the techniques used to capture, confine, manipulate and detect the ions inside the Penning trap. We give an over-view of the status of the project and the planned procedures to measure the laser-focus shape in situ.